DIURGENSI PENINGKATAN PEMANFAATAN PELABUHAN TAPAKTUAN KABUPATEN ACEH SELATAN PROVINSI ACEH - Medi Nopiana (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2017)
This review discusses the potential of South Aceh Regency generated by the economic sectors above. In addition, this study will discuss the current condition of Tapaktuan Port as well as the direction of development policy of South Aceh Regency to improve the utilization of Tapaktuan Port. The method of analysis in this research uses descriptive method, based on a series of data collection methods through literature study, observation and interview. Increased utilization of Tapaktuan Port still faces a number of challenges, including the non-functioning of Tapaktuan as a center of growth and economic accumulation of South Aceh Regency. Therefore. the need for the South Aceh Regency Government to consistently implement policies concerning the utilization of Tapaktuan Port, as well as create strong synergy between the government of South Aceh district with the central government in order to develop trade (ships follow the trade) and grow the less developed areas (ships promote the trade). Keywords: Tapaktuan Port, Regional Potential, Aceh Selatan Regency